The Implementation of Using Flash Card in Teaching Writing - Berliana Febriyanti; Mariyatul Kiptiyah; Moh. Arief Wahyudi (Penerbit STKIP PGRI Bangkalan, 2022)
This study aims to determine the feasibility of implementing flascards in teaching riting skills. The qualitative descriptive was used in this study by using content analysis. The technique of obtaining data used documentation. The data were analyzed by coding, displaying, and making verification. The data analysis was carried out in depth by using some theories related to the flashcards in teaching writing skills. The results of the study indicate the interrelation of the implementation and responses of the students in using flashcards. The flashcards is very helpful for students in learning to writing English because it is based on the examples given and they have learnt identifying patterns in writing skill. By seeing some journals stated that using Flashcard can improve writing skills and knowledge of vocabularies. Furthermore, it is suggested that flashcards can be effectively used in writing class.